2017
DOI: 10.1080/10826084.2017.1387569
|View full text |Cite
|
Sign up to set email alerts
|

Positive Affect as a Predictor of Smoking Cessation and Relapse: Does It Offer Unique Predictive Value among Depressive Symptom Domains?

Abstract: With the exception of PA, all of the CES-D domains predicted reduced likelihood of smoking abstinence at end of treatment and cotinine-confirmed (but not self-reported) abstinence at 6 months, as did total CES-D score (all p-values < .05). None of the symptom domains predicted relapse. Conclusions/Importance: Our results provide further evidence that current depressive symptoms predict worse cessation outcomes, but they fail to support recent work suggesting that low PA has incremental predictive value for ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…PA is distinct from negative affect both conceptually and empirically [48]. Some studies have suggested that low PA prior to smoking cessation treatment may have a unique association with poor smoking outcomes independent of depressive symptoms [4], although a recent study did not support this conclusion [49]. Both reductions in PA leading up to quit date and low PA after quitting have been implicated in smoking relapse [5, 50].…”
Section: Methodsmentioning
confidence: 99%
“…PA is distinct from negative affect both conceptually and empirically [48]. Some studies have suggested that low PA prior to smoking cessation treatment may have a unique association with poor smoking outcomes independent of depressive symptoms [4], although a recent study did not support this conclusion [49]. Both reductions in PA leading up to quit date and low PA after quitting have been implicated in smoking relapse [5, 50].…”
Section: Methodsmentioning
confidence: 99%
“…The numerous evidences in the literature pointing to an important role for Anxiety and Depression in tobacco addiction corroborate the findings of this study, and are additional justifications for incorporation of such elements into SET. [22][23][24][25][26][27] The factor Attachment to Cigarettes derived from the measurement Affiliative Attachment, a constituent of scales developed to characterize reasons for smoking. 16,28 In addition, there are suggestions that smokers can anthropomorphize cigarettes and see them as companions in response to loneliness, using them to meet social needs.…”
Section: Pleasure Of Smokingmentioning
confidence: 99%
“…Novel interventions are needed to target the key factors that maintain smoking, including depressive symptoms, which are present in 40% to 55% of treatment-seeking smokers [4,5]. Depressive symptoms at the time of a quit attempt, including high negative affect (ie, aversive internal states such as anxiety or sadness) and low positive affect (ie, reduced experience of pleasure or enthusiasm), reduce the odds of smoking cessation by as much as 50% [4,6-8]. Failure to address depressive symptomatology as a barrier to quitting is a significant problem with the current standard treatment approach.…”
Section: Introductionmentioning
confidence: 99%
“…At present, BAT-D–based smoking cessation interventions have solely been tested as a face-to-face treatment, which would reach only 4% to 6% of smokers in the United States based on current use of the traditional treatment modalities of individual and group counseling [3,14,15]. We developed a BAT-D mobile health (mHealth) app for smoking cessation to extend the reach of this promising intervention to the estimated 13 to 16 million smokers with smartphones who have depressive symptoms [8,15-17], the vast majority of whom will not seek face-to-face counseling. BAT-D is a promising treatment approach for a targeted mHealth smoking cessation intervention because it has shown promise helping smokers with depressive symptoms quit smoking in the face-to-face format [9,13], its components are well suited to translation into an app (eg, scheduling valued activities and tracking their completion), and it has a strong foundation in behavioral theory [11].…”
Section: Introductionmentioning
confidence: 99%